Indonesia's Free and Active Foreign Policy is the Basis for Realizing World Peace - Susilawati, Susilawati; Yusuf, Rizal; Rachman, Arief (PT FORMOSA CENDEKIA GLOBAL, 2024)
The key to world peace is living peacefully side by side between fellow countries in the world and not disturbing each other. The character of the Indonesian nation is the potential to become superior diplomats in various fields of life and can influence the world to live life in a spirit of humanity and nobility regardless of culture, ethnicity, religion, nation, race and status in order to realize world peace. This spirit will enable Indonesia's free and active foreign policy to be implemented effectively and provide positive results and benefits for the Indonesian nation and other peoples in the world.